Synthesis, characterization, colorimetric sensor and acetylcholinesterase inhibition studies of novel benzimidazole-based hydroxamic acids - Yilmaz, Fatih; Kizil, Demet; Dincer, Barbaros; Karaoglu, Kaan (Elsevier, 2025)
Two new hydroxamic acid molecules 2-(2-Pyridyl)benzimidazole-N-acetohydroxamic acid (HL1), 2-(2-Pyridyl) benzimidazole-N-butanohydroxamic acid (HL2), can be used in Fe(III) detection and pest control, have been synthesized first time and characterized using Elemental Analysis, 1H NMR, 13C NMR, FT-IR, LC-MS (ESI+) spectrometry. Selectivity of the HL1 and HL2 towards Fe3+ ion were tested against in the presence of the competitive metal ions and found to be highly effective agents for the determination of Fe3+ ions in the presence of these ions. The limits of detection of Fe(III) ions using these ligands were found 1.9 mu M and 0.7 mu M, respectively. Metal complexes of HL1 and HL2 with Fe(III), Co(II), Ni(II), Cu(II), Zn(II), and Cd(II) were also synthesized to understand the complex formation in the solid phase and at higher pH. The results showed in the solid phase the M:L ratios of the complexes were 1:1 and 1:2 and the hydroxamate groups were in the keto form. The inhibition effects of HL1 and HL2 ligands on acetylcholinesterase (AChE) purified from Orosanga japonica (Melichar, 1898) (Homoptera: Ricaniidae) were determined. The ligands effectively inhibited acetylcholinesterase yet HL1 was more effective than HL2, IC50 values of 1.7 +/- 0.2 mM and 2.6 +/- 0.1 mM, respectively. These results indicated these newly synthesized benzimidazole-based hydroxamic acid ligands can serve as dualfunctional agents for both Fe3+ detection and pest control.
Keywords: Hydroxamic acid; Hydroxamate; Colorimetric sensor; Benzimidazole; Acetylcholinesterase inhibition